Relation between ADAMTS13 activity and ADAMTS13 antigen levels in healthy donors and patients with thrombotic microangiopathies (TMA) - Rieger, Manfred; Ferrari, Silvia; Hovinga, Johanna A. Kremer; Konetschny, Christian; Herzog, Andrea; Koller, Letizia; Weber, Alfred; Remuzzi, Giuseppe; Dockal, Michael; Plaimauer, Barbara; Scheiflinger, Friedrich (Thrombosis and Haemostasis, 2006)
We have established a new, enzyme-linked immunosorbent assay (ELISA) for the detection of ADAMTS13 antigen using purified polyclonal rabbit anti-human ADAMTS13 IgG. Normal plasma ADAMTS13 antigen levels span a concentration of 740 –1420ng/ml (median 1080ng/ml) resulting in an ADAMTS13 activity to antigen ratio of 0.48 to 1.68 U/µg. In a cohort of HUS patients, ADAMTS13 antigen was in the normal range, whereas in hereditary TTP patients antigen levels were low to undetectable, in concordance with severe deficient ADAMTS13 activity. Plasma of acquired TTP patients was found to contain free as well as autoantibody-bound ADAMTS13. We also present evidence for circulating anti-ADAMTS13 antibody/ADAMTS13 antigen immune complexes not only in acutely ill or actively treated patients but also in patients who have already achieved clinical remission. This new developed ADAMTS13 antigen ELISA assay allows rapid determination of ADAMTS13 antigen levels in human plasma but is of limited predictive value for the diagnosis or treatment of acquired TTP due to the detection of ADAMTS13 in antibody complexes.
Keywords: ADAMTS13; ADAMTS13-antigen; ELISA; TTP; HUS